Nest Characteristics of the Sumatran Orang-utan (Pongo abelii) in the Wildlife Sanctuary Soraya Station in Aceh Province, Indonesia - Rita Andini; Erdiansyah Rahmi; Mardiana; Saida Rasnovi; Martunis; Ryan Moulana (Tropical Life Sciences Research, 2021)
Orangutans (Pongo spp.) populations used to be widely distributed throughout Southeast Asia, from Java in the south to the southern China in the north during the Pleistocene. Their populations have declined up to 75% of their original size and are now distributed only in parts of the tropical rainforests of Borneo and Sumatra. Pongo pygmaeus, Pongo tapanuliensis and Pongo abelii, are the three most representative species, and this study discussed the latter. Sumatran forests are generally suffering from deforestation with rates ranging from 3.74% to 49.85% between 2000 and 2012. Thus, human wildlife conflict intensity has escalated and gained more traction. Orangutans are known as arboreal great apes and need to build nests for resting. Here we applied the transect line method (three transects; each 1,000 m long) at different elevations in Soraya Station, Gelombang Village, Sultan Daulat sub-district, Subulussalam district, and assessed nest characteristics. The characteristics are: (1) nesting position referring to the position of nest on a tree; (2) nest successional stages defining the age and leaf decay used in constructing a nest indicated with I (new) until V (almost gone); and (3) nest density to predict the density of nest per square km. Afterwards, the identified nesting trees along the transect were further identified based on their species, and assessed based on three characteristics (the nesting tree height, diameter and the height of a nest measured from the soil). A total of 27 nests were found, and 44% were located in transect III or at the riparian. Out of 27, four orangutans’ nests were found on Moraceae (Streblus elongatus) and Myrtaceae (Syzigium spp.), while three nests were found on Dipterocarpus sp. Tree height, tree diameter and nest height were 10 m–25 m (mean = 17.5 m; SD = ± 0.25), 10 cm–30 cm (mean = 20 cm; SD = ± 0.4) and 16 m–20 m (mean = 18 m; SD = ± 0.35), respectively. Meanwhile, nest density calculated based on the form: d = [N/ (L* 2w)], and the values obtained were 8.4, 13.45, 26.9 nests/km2 located on transect I, II and III or at the riparian. The most commonly found nest successional stages and position were stage III and position 3, respectively. This study could serve as baseline research representing that in primate conservation, nest characterisation could be used as guidance for any future activity planning (e.g., tree reforestation) in a particular region and the existence of various tree species diversity are indispensable for maintaining orangutan habitats’ quality.